Pergulatan Advokasi Kebijakan Pengarusutamaan Gender di Kota Pekanbaru - Harirah. MS, Zulfa; Marta, Auradian; Isril, Isril (Pencerah, 2023)
Gender inequality has not become a priority issue in Pekanbaru City. The percentage of gender mainstreaming that is included in the work programs and activities of regional apparatus organizations is only around 48%. BPS data shows an increasing trend of the Gender Development Index in 2021, namely 93.27 from 93.01 in 2020. But the Gender Empowerment Index in Pekanbaru City has actually decreased in 2021, namely 68.63 percent from 69.23 in 2020. Gender mainstreaming has become a strategy to reduce gender inequality for nearly ten years. However, this advocacy has not been able to integrate gender mainstreaming in every regional policy in Pekanbaru City. For this reason, this research will find advocacy struggles that occur by mapping the power and interests of stakeholders. This research is qualitative research by conducting interviews with 5 informants from related agencies and collecting secondary data. Then various data and information were analyzed using advocacy theory and Power-Interest Stakeholders according to Ackermann and Eden (2011). The results of the study show that the power and interests of stakeholders in implementing gender mainstreaming in Pekanbaru City are still low. This is evidenced by the fact that only a few DPOs have integrated gender equality into gender-responsive planning and budgeting.